﻿L’exposition de la modernité artistique, lieu de construction de l’identité nationale - Couture, Francine (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1994)
This article investigates the relation between art exhibitions and political issues by analysing a few exhibitions with titles referring to national identity, such as La peinture canadienne moderne. 25 années de peinture au Canada français, Canada 101 and Canada, art d’aujourd’hui. These exhibitions were organized during the sixties by both Canadian and Quebecois governmental agencies and were intended to be seen abroad. Within the paradoxical modernist duality, in which modernity is presented as both nationally rooted and internationally defined, such exhibitions raised the issue of national identity. The communities of taste that received the mandate of organizing these events tried to impose what they each considered as the genuine definition of Canadian artistic modernity. An intense confrontation and renewal of Canadian and Quebecois nationalisms characterized this period.Thus, this article examines how exhibitions may receive political signification through their setting, the social conditions in which they were held and the discourse produced to accompany them. These exhibitions also participated in the definition of both new Canadian and new Quebecois national identities, each of them being involved in a transforming process.